ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI IMPLEMENTASI KEBIJAKAN SISTEM PELAYANAN TERPADU SATU PINTU (PTSP) PADA LAYANAN UPT PERPUSTAKAAN UNIVERSITAS ANDALAS - Larasati Larasati; Ardoni (Program Studi Perpustakaan dan Ilmu Informasi, Fakultas Bahasa dan Seni, Universitas Negeri Padang, 2022)
This study aims to analyze the influence of Andalas communication, analyze the influence of Andalas resources, analyze the influence of dispositions, analyze the influence of bureaucratic structures and analyze communication, resources, dispositions, and bureaucratic structures simultaneously on the implementation of the One Stop Service (PTSP) policy at UPT Library Andalas University. This type of research is quantitative research. The population in this study were the Coordinators and all One Stop Service (PTSP) officers at UPT Andalas University, totaling 9 people. The instruments used in this study used observation guidelines, questionnaire guidelines, and interview guidelines. Data collection techniques were carried out by means of observation, questionnaires, and interviews. The data analysis requirements test in this study is the instrument test, the classical assumption test and the hypothesis test. The steps to analyze the data are data collection, editing, coding, tabulating data, testing data quality, describing data and testing hypotheses. The results of the research show that communication, resources, position have no effect on policy implementation. While bureaucratic structure influences policy implementation, communication, resources, position and bureaucratic structure together show a large influence on policy implementation.